PENGARUH RASIO KOMPOSISI LIMBAH PLASTIK DAN SERBUK KAYU TERHADAP KARAKTERISTIK MEKANIK KUAT TEKAN SEBAGAI MATERIAL BANGUNAN RINGAN - Darasita Zahra Dayanun (Hexagon, 2025)
This study aims to examine the effect of the ratio of plastic waste and sawdust on the mechanical characteristics of alternative lightweight building materials. Plastic waste is used as a thermoplastic binder, while sawdust acts as a lightweight aggregate with insulating properties. The composition of the mixture is varied in several ratios (90:10, 80:20 and 70:30) to determine its effect on the mechanical properties of compressive strength test specimens according to SNI 03-3958:1995 from the resulting mortar product. The manufacturing process involves mixing melted plastic waste with sawdust, then molding and releasing. The test results show that increasing the proportion of sawdust can significantly reduce the compressive strength. Conversely, a higher plastic ratio increases the compressive strength but produces a heavier material. The optimum composition was found at a ratio of 90:10 (plastic: sawdust), which provides a balance between strength, lightness, and insulating properties. This study shows the potential for utilizing plastic waste and sawdust as environmentally friendly building materials with feasible functional performance and in accordance with compressive strength standards.